Design of Negative Resistance Oscillator with Rocord Low Phase Noise - Ayoub Malki; Jamal Zbitou; Larbi El Abdellaoui; Mohamed Latrach; Abdelali Tajmouati; Ahmed Errkik (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The aim of this paper is to use a new design of a negative resistance microwave oscillator in order to fabricate oscillator with very good performance in terms of output power, efficiency, stability and phase noise. In this study the new concept of oscillator using distributed resonator and micro-strip circuit elements improve performances of our structure. A micro-strip microwave oscillator with low phase noise based on an NPN silicon planar epitaxial transistor has been designed, fabricated, and characterized. In this design, each step has been conducted by using Advanced Design System (ADS) and following a theoretical study which enable to optimize the different performances of the whole circuit. The oscillator produce a sinusoidal signal with spectrum power of 12.25 dBm at 2.45 GHz into 50 Ω load when polarized at Vcc=15V with DC to RF efficiency of 16. The obtained phase noise of -120 dBc/Hz at 100 Hz offset is the result of the use of high Q factor resonator and the depth study of the parameters of the oscillator. Simulation and measurement results are in good agreement.